Surgical management Of Omphalitis In Calves - Prasanna D (Department of Surgery and Radiology, College of Veterinary and Animal Sciences, 2003)
The study was carried out in twelve . selected clinical cases of umbilical infections in calves of different breeds of either sex presented to the Veterinary College Hospitals at Mannuthy and Kokkalai. These animals were divided into two groups viz., Group I and Group II, each consisting of six animals. In Group I, the calves with extra-abdominal umbilical infection and in Group II, the calves with combined extra-abdominal and intra abdominal umbilical infections were included. The calves in Group I were within the age group of eight weeks and had the history of swelling at the umbilicus for at least a period of eight days which varied in its type, consistency, and tenderness on palpation. The size of the swelling was maximum of 10.5 cm in diameter with no connection or extension into the abdominal cavity. The swelling was either draining to the exterior through a fistula or closed. The cavity of the swelling was from 3.4 cm to 15 cm in length containing pus which varied in its consistency, color and odour. The physiological parameters were all within normal range. The haemogram was also within physiological range except for an increase in the neutrophil count. Abdominal palpation and retrograde contrast radiography confirmed that the swelling is confined to the exterior of the abdomen. The causative organisms were detected and the calves were successfully treated